The effect of the local economic context and local public services on financial satisfaction among youth in European cities - Medgyesi, Márton; Csathó, Ábel (Frontiers in Sociology, 2024)
The post-2008 economic recovery period has seen varying degrees of improvement in the well-being of young individuals across different countries, regions, and cities of the EU. This study contributes to the literature on the geography of well-being by examining the impact of urban economic contexts on the subjective well-being of youth in Europe, a topic that has received limited attention so far. Specifically, we investigate how the local economic context has affected financial satisfaction among the young (15–35 age group) in European cities during the recovery period after the economic crisis. We study whether living in a city with better opportunities in the labor market, on the housing market, or with better local services (e.g., education or health care) affect financial satisfaction among the young. We carried out multilevel analysis of financial satisfaction among young adults on data from the Quality of Life in European Cities survey (years 2012, 2015, 2019), which asks about aspects of quality of life among a representative sample of the population in a large number of cities in EU Member States. Overall, the results suggest that a better labor market context (where it is in general easier to find a job) has a statistically significant positive effect on financial satisfaction among the young. Our results also show that satisfaction with the financial situation among young adults is significantly higher in cities with a higher quality of local social services. On the other hand, we have found only small (and statistically non-significant) contextual effect related to the local housing market.